INITIAL GROWTH OF Citharexyllum myrianthum plants UNDER PLANTING FERTILIZATION - Silva, Oclizio Medeiros das Chagas; Leles, Paulo Sérgio dos Santos; Lopes, Lucas Nunes; Santos, Gilsonley Lopes dos; Delgado, Lucas Britto; Silva, Eduardo Vinicius da (Floresta, 2023)
The objective of this work was to evaluate the initial growth of Citharexyllum myrianthum under the influence of three sources of planting fertilizers, in conditions of 18 L pots. The treatments used were, as follows: absolute control; 5 L of biosolid/pot; 300 g of natural rock phosphate (NRP), and 200 grams of NPK 06-29-06. The seedlings were grown in pots in full sun, supplemented with Dystrophic Red Yellow Latosol. At 150 days after transplanting, the plants were measured, obtaining the height of the aerial part and the diameter of the stem. Then, the increment of these two variables was calculated. Subsequently, the leaves were removed to determine the leaf area (LA), separating the aerial part from the root system, and then packed in a paper bag and placed in an oven at 65ºC, for drying until reaching constant weight. After weighing this material to obtain the dry matter of the aerial part (APDM) and root (RDM). The leaves were ground to determine the foliar contents of N, P, K, Ca, and Mg. To evaluate the effect of treatments on the soil, samples were taken from the pots to determine the levels of macronutrients, organic matter, and CEC(t). It was found that the LA and APDM of plants fertilized with NPK showed significantly higher values when compared to plants cultivated in the control treatment. It is recommended to fertilize Citharexyllum myrianthum plants with 200 grams of N-P-K 06-29-06/hole or with 5 L of biosolid.